概日リズムによって制御された細胞増殖ダイナミクスに対するガン時間治療効果のシミュレーション - 中尾, 光之; 辛島, 彰洋; 片山, 統裕; 井ノ川, 広 (Transactions of Japanese Society for Medical and Biological Engineering, 2015)
It has been reported that therapeutic value of cancer chemotherapy depends on a period of treatment time of the day. This effect, circadian time-dependency of treatment, has been considered to come from interactions between cell cycle and circadian rhythm. In this study, we aimed to clarify a biological background of this effect by means of simulating therapeutic effect based on a model of cell cycle controlled by circadian rhythms. Here we constructed a cell proliferation model using a framework of stochastic automaton. During the cell cycle process, a cell is subject to DNA damage with a certain probability. Then the damaged cell dies or returns to the cell cycle, causing a phase response to the cellular circadian clock system. In the simulations, a cancer cell is characterized by prolonged or shortened duration of G1 phase of the cell cycle. We simulated proliferation of 10,000 cells population treated by a drug that increases death rate of cells in S phase. As a result, we found that morning treatment is most effective to maximize the damage to the cancer cells and minimize the normal cell's death.